Biotransformation of major ginsenoside Rb1 to pharmacologically active ginsenoside Rg3 through fermentation by Weissella hellenica DC06 in newly developed medium (Bangladesh Journal of Scientific and Industrial Research, 2016)
The study was conducted to develop an edible and low cost growth medium for cultivation of Weissella hellenica DC06, a lactic acid bacteria (LAB) and to study whether, the medium is suitable for bioconversion of major ginsenoside Rb1 into ginsenoside Rg3 through fermentation by W. hellenica DC06. Fourteen different media compositions were investigated to cultivate W. hellenica DC06. Among these, W. hellenica DC06 exhibited the highest growth in media containing 20 g/l radish, 20 g/l glucose, and 10 g/l yeast extract (Medium 3). The optical density of W. hellenica DC06 cultivated in medium 3 reached 1.8 (1.066 x 1010 CFU/ml) after 24 h of incubation. Importantly, the optimized medium was approximately four times cheaper compared to MRS medium. In addition to being economical, the new medium was also edible. Also W. hellenica DC06 showed strong fermentation ability in newly developed medium regarding on major ginsenoside Rb1 biotransformation. Ginsenoside Rb1 was converted into pharmacologically active ginsenoside Rg3 in new medium. In contrast,W. hellenica DC06 showed weak fermentation ability in MRS medium where ginsenoside Rb1 was converted intoginsenoside Rd. The transformation products were analyzed by TLC, and HPLC. Within seven days of fermentation, almost all ginsenoside Rb1 was decomposed and converted into Rg3 in optimized medium. W. hellenica DC06 hydrolyzed two glucose moieties attached to the C-20 position of the ginsenoside Rb1aglyconeand synthesized Rg3 in newly developed medium.Bangladesh J. Sci. Ind. Res. 51(4), 271-278, 2016